Calcineurin Inhibitors Associated Posterior Reversible Encephalopathy Syndrome in Solid Organ Transplantation: Report of 2 Cases and Literature Review. Issue 14 (April 2016) - Song, Turun; Rao, Zhengsheng; Tan, Qiling; Qiu, Yang; Liu, Jinpeng; Huang, Zhongli; Wang, Xianding; Lin, Tao
Abstract : Abstract: Posterior reversible encephalopathy syndrome (PRES) is a rare neurologic side effect of calcineurin inhibitors (CNIs) with poorly understood clinical features. We report cases of 2 patients with PRES developing after kidney transplantation and summarize PRES clinical features through a literature review. The 1st case was a 28-year-old man who received a kidney transplant from a deceased donor. Initial immunosuppressive therapy consisted of tacrolimus/mycophenolate mofetil/prednisolone. He developed headache and blurred vision with visual field loss15 days after transplantation and generalized seizures 4 days later. The 2nd case was a 34-year-old man who received a living kidney transplant. His initial immunosuppressive therapy comprised tacrolimus/mycophenolate mofetil/prednisolone. Two months after transplantation, he developed seizures. Both patients were diagnosed with PRES based on neurological symptoms and magnetic resonance imaging (MRI) findings; they recovered after switching from tacrolimus to either a cyclosporine or a lower tacrolimus dose. CNI-associated PRES is an acute neurological syndrome with seizures, encephalopathy, visual abnormalities, headache, focal neurological deficits, and nausea/vomiting. It is always accompanied by hypertension. A fluid-attenuated inversion recovery signal MRI scan typically shows reversible subcortical white matter changes in the posterior cerebral hemisphere that usually occur within the 1st month after transplantation. CNI-associated PRES has a generally favorable prognosis with early diagnosis and prompt treatment including alternating or discontinuing CNIs and blood pressure control. CNI-associated PRES should be considered in patients exhibiting acute neurological symptoms after transplantation. Early diagnosis and immediate treatment are critical for a favorable prognosis.